The Application of the Dimensional Analysis Approach in Understanding the Interrelationships Between Physical Quantities for Students - Lega Serano, Havez Rasya; Suhendi, Endi; Ramdhania, Lathifa Nur; Sari, Lasmita; Amiruddin, Mohd Zaidi Bin; Sya’roni, Imam (Universitas Lambung Mangkurat, 2026)
The main issue raised in this study is the tendency of students to rely on memorizing physics formulas without understanding the relationships between quantities and their dimensions. This study aims to explore the use of the dimensional analysis approach as a tool for understanding and deriving the relationships between physical quantities in various types of motion, including oscillatory motion, free fall motion, and parabolic motion. Exploratory and conceptual analysis methods were used in this study with a descriptive approach. In addition, an attitude scale instrument was used to measure students’ perceptions, which has been shown to be valid (0.80–0.92) and reliable (α = 0.89). The results show that the equations obtained through dimensional analysis are consistent with theoretical equations. This confirms that the approach is capable of correctly identifying the form of physical relationships, although it cannot yet determine the numerical constants precisely. In addition, student responses show a positive attitude towards the dimensional analysis approach, which is considered a new, useful, and efficient way of solving physics problems. However, students also recognized the limitations of this method in producing exact solutions due to the existence of arbitrary constants. These findings indicate that dimensional analysis is a scientifically robust and pedagogically valuable approach that can strengthen conceptual understanding. Thus, the application of the dimensional analysis approach in physics learning can help students find solutions logically and systematically.